2017
DOI: 10.14814/phy2.13513
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle myosin 2 proteins encoded by Myh9 , Myh10 , and Myh14 are uniquely distributed in the tubular segments of murine kidney

Abstract: The diverse epithelial cell types of the kidneys are segregated into nephron segments and the collecting ducts in order to endow each tubular segment with unique functions. The rich diversity of the epithelial cell types is highlighted by the unique membrane channels and receptors expressed within each nephron segment. Our previous work identified a critical role for Myh9 and Myh10 in mammalian endocytosis. Here, we examined the expression patterns of Nonmuscle myosin 2 (NM2) heavy chains encoded by Myh9, Myh1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…As both scRNAseq and CISH indicated, UIR caused a marked Myh9 elevation in all renal tubule compartments, including the sub-clusters of injured and dedifferentiated proximal tubules, and in the collecting ducts ( Figures 5D and 5E). Importantly, previous work specifically reported that Myh9 expression is absent in normal proximal tubules (Otterpohl et al, 2017). We validated the injured proximal tubule expression via co-staining the Myh9 CISH with Aqp1 IF and identified Aqp1-positive proximal tubules exhibiting elevated Myh9 expression which was not detected in the control ( Figure 5F), providing an additional evidence for the injury induced mesenchymal phenotype in renal epithelial tubules.…”
Section: Novel Gene Expression Signatures Of Akisupporting
confidence: 59%
“…As both scRNAseq and CISH indicated, UIR caused a marked Myh9 elevation in all renal tubule compartments, including the sub-clusters of injured and dedifferentiated proximal tubules, and in the collecting ducts ( Figures 5D and 5E). Importantly, previous work specifically reported that Myh9 expression is absent in normal proximal tubules (Otterpohl et al, 2017). We validated the injured proximal tubule expression via co-staining the Myh9 CISH with Aqp1 IF and identified Aqp1-positive proximal tubules exhibiting elevated Myh9 expression which was not detected in the control ( Figure 5F), providing an additional evidence for the injury induced mesenchymal phenotype in renal epithelial tubules.…”
Section: Novel Gene Expression Signatures Of Akisupporting
confidence: 59%
“…Conditional genetic inactivation of Myh9 (NM2A) and Myh10 (NM2B) in adult mouse renal epithelia results in progressive kidney disease. MYH9&10 proteins have a partially overlapping expression pattern in murine tubular epithelial segments (15). In order to uncover redundant functions of NM2 proteins in the kidney epithelial compartments, as well as to model a severe loss-of-function phenotype, we inactivated both alleles of Myh9 and Myh10 only in the adult renal epithelium.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of MYH9&10 proteins in mouse renal tubules results in intracellular accumulation of glycosylphosphatidylinositol-anchored protein UMOD and gradual loss of NKCC2 in the TAL. MYH9 (NM2A) and MYH10 (NM2B) are both expressed in the mouse TAL segment (15); therefore, we assessed the localization and expression pattern of the major TAL-specific membrane-associated proteins. UMOD is a unique glycosylphosphatidylinositol-anchored (GPI-anchored) protein in the TAL segment that undergoes N-glycosylation(s) and as a mature protein has a 16-to 24-hour turnover rate on the apical membrane (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, MYH14 encodes for a heavy chain that is an integral component of nonmuscle myosin 2, a protein essential for kidney development and function (44,45). When evaluated in mice, Myh14 was expressed throughout most segments of the renal tubules, and was implicated in the regulation of the renal epithelial transport process (46). Because cisplatin is excreted from the body predominantly through renal clearance, the importance of genetic architecture surrounding kidney development and function is apparent, and could markedly influence long-term platinum kinetics and circulation in serum.…”
Section: Discussionmentioning
confidence: 99%